Seeing to it that an agent forms a belief - Wansing, Heinrich (Logic and Logical Philosophy, 2004)
To what extent, if any, is belief formation under our direct voluntary control? In the present paper, it is suggested that an understanding of ascriptions of an agent α’s belief formation can be obtained by considering ascriptions of α’s seeing to it that α has certain implicit beliefs. It will turn out that, contrary to what doxastic anti-voluntarists such as B. Williams have claimed, a consistent formal treatment of ascriptions of belief formation, understood as decisions to believe, is possible.